Atumics Methods Implementation: Work and Eat Activity Improvement in Warunk Upnormal as Study Case - Erlana Adli Wismoyo; Mahendra Nur Hadiansyah; Ahsana Putri; Faridah Awaloka; Lilyana Yashila; Rizka Nurul (Departement of Architecture, Universitas Islam Indonesia, 2024)
This article aims to improve the quality of eating and working activities provided by restaurants/cafes in their indoor facilities by using one of the furniture objects in the Warunk Upnormal case study as study material. It starts by analysing consumer activities and their relationship to the facilities provided by the service provider. Warunk Upnormal in its marketing campaign informs about activities that can be accommodated by its consumers, including eating, gathering, working, etc. In a survey conducted on a sample of these consumers, it is stated that the dominant activities are eating, drinking, and working. With this background, data collection related to profiles, activities, and activity support facilities was carried out through direct observation and online surveys using convenience sampling techniques. The literature on dining table facilities as a medium that accommodates activities is also studied. Ergonomic data on dining and worktable artifacts, and supporting tools for eating, drinking, and working activities were collected. These data were analysed through the revitalization method of traditional design, called ATUMICS, where this method is a method used to design new artifacts with an innovation orientation that refers to certain intentions or goals. Dining table innovation supports eating and drinking activities, and this work aims to accommodate these activities so that they can be carried out comfortably and productively. Adjustment of ATUMICS elements is applied to the design, which includes elements of technique, utility, materials, concept, and shape. In conclusion, it is found that by using the ATUMICS method the dining table object in the restaurant/cafe can be adapted to the service facilities provided by the restaurant/cafe so that consumers can carry out their activities optimally. Keywords: activities; consumer; design; dining table; furniture; innovation; productivity